Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Tingkat Kepuasan Konsumen dan Dampaknya Terhadap Loyalitas Pelanggan (Studi Empiris pada Pizza Hut Duta Pertiwi Mall Semarang) - Cefiro, 08.05.51.0141 Roval Allenby; Yulianto, Heru (Students Journal of Economic and Management, 2012)
Todays the businessâs competition is becoming intense. Including competition in food business. Pizza Hut is a services company specializing in food and baverages are very high regard of quality service and products. This research aims to find out whether the product quality and service quality of positive influential to consumerâs satisfaction and customer satisfaction influential favorably to loyality. Therefore this research took the title âInfluence of Product Quality and Service Quality Toward Customer Satisfaction and Its Impact on Customer Loyalty (Empirical Study At Pizza Hut Duta Pertiwi Mall)". Samples in this study set a number of 100 respondents, using the technique of Purposive Sampling sample. And data collection techniques in the research is kuisioner. The results of hypothesis testing showed a partial positive and significant between product quality and customer satisfaction are partially influence the quality of service with customer satisfaction as well as customer satisfaction and loyalty. The results of testing the hypothesis that there is simultaneously showed positive and significant relationship between product quality and service quality to customer satisfaction, and between customer satisfaction to loyalty.Key words: product quality, service quality, customer satisfaction and loyalty